2017
DOI: 10.1039/c6qo00851h
|View full text |Cite
|
Sign up to set email alerts
|

I2-Catalyzed sulfenylation of indoles and pyrroles using triethylammonium thiolates as sulfenylating agents

Abstract: Readily available triethylammonium thiolates were proven to be new and eco-friendly sulfenylating agents for the efficient and practical construction of sulfenylated indoles and pyrroles (48 examples) with good to excellent yields under metal-free and microwave irradiation conditions. The combination of I2 and DMSO enabled direct C-S bond formation, allowing easy and low-cost access to new functionalized C,S-tethered bisindoles and pyrrole-indole pairs with a wide diversity of substituents. The mechanism invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…In 2017, Li and co‐workers reported an iodine‐promoted intermolecular C(sp 2 )−S bond coupling for the synthesis of 3‐thiolated indoles and pyrroles under microwave irradiation, with triethylammonium thiolates as the reliable sulfenylating reagents (Scheme 34). [88] Under standard conditions, various C,S‐tethered bisindoles 103 and pyrrole‐indole pairs 105 were obtained in relatively good yields. In the control experiments, no obvious change of the reaction was observed in the presence of TEMPO or BHT, which suggested that no radical process was involved in this transformation.…”
Section: Iodine‐promoted C−s Bonds Formationmentioning
confidence: 99%
“…In 2017, Li and co‐workers reported an iodine‐promoted intermolecular C(sp 2 )−S bond coupling for the synthesis of 3‐thiolated indoles and pyrroles under microwave irradiation, with triethylammonium thiolates as the reliable sulfenylating reagents (Scheme 34). [88] Under standard conditions, various C,S‐tethered bisindoles 103 and pyrrole‐indole pairs 105 were obtained in relatively good yields. In the control experiments, no obvious change of the reaction was observed in the presence of TEMPO or BHT, which suggested that no radical process was involved in this transformation.…”
Section: Iodine‐promoted C−s Bonds Formationmentioning
confidence: 99%
“…In 2017, Li and Jiang group, discussed easily acessible triethylammonium thiolates as new and ecologically sound sulfenylating agents for well‐planned and experimental metal‐free and microwave assisted preparation of sulfenylated pyrroles with moderate to fabulous yields (Scheme 129). [146] …”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…Synthesis of 3‐sulfenyl indoles from indoles and thiols with the use of the I 2 /DMSO system was carried out in DCE at 60 °C and provided sulfenylated products in 67–96 % yields [20] . The same system was applied for the sulfenylation of indoles at the 3 d position with triethylammonium thiolates under microwave irradiation [21] . The I 2 /H 2 O 2 system was also proposed for the synthesis of 3‐sulfenyl indoles [22] .…”
Section: Thiols As Sulfenylating Agentsmentioning
confidence: 99%